2017
DOI: 10.22219/jpbi.v3i1.3905
|View full text |Cite
|
Sign up to set email alerts
|

The effect of project based learning model in seminar course to student’s creative thinking skills

Abstract: The purpose of this study was to determine the effect of Project Based Learning model of the student’s creative thinking skills. The methode used in this research was quasi-experimental. Subjects in this study were the seventh semester students of class C the experimental class and class A as the control. The results indicated that there was a significant increase of student’s creative thinking skills in experimental class compared to the control class which was indicated by N-gain test result (0.004 <0.05)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 2 publications
1
11
0
2
Order By: Relevance
“…During project activities, they were encouraged to actively reflect their knowledge and have the awareness to collaborate in groups. Collaborative activities in solving problems through project activities are known to be able to educate students to become active learners (Amin & Adiansyah, 2018;Antika & Nawawi, 2017;Bell, 2010;Kokotsaki et al, 2016;Ramdiah, Abidinsyah, & Mayasari, 2018). This collaboration activity was also reportedly capable to optimize the process of absorbing knowledge during learning (Krishnan, Gabb, & Vale, 2011;L.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…During project activities, they were encouraged to actively reflect their knowledge and have the awareness to collaborate in groups. Collaborative activities in solving problems through project activities are known to be able to educate students to become active learners (Amin & Adiansyah, 2018;Antika & Nawawi, 2017;Bell, 2010;Kokotsaki et al, 2016;Ramdiah, Abidinsyah, & Mayasari, 2018). This collaboration activity was also reportedly capable to optimize the process of absorbing knowledge during learning (Krishnan, Gabb, & Vale, 2011;L.…”
Section: Resultsmentioning
confidence: 99%
“…The influence of Hybrid-PjBL implementation on students' creative thinking skills is in line with several previous reports that examine the use of PjBL and hybrid learning to thinking skills. Antika & Nawawi (2017) and Rambely et al (2013) emphasize that PjBL is able to empower students' creative thinking skills. In line with these findings, Husamah (2015b) also suggests that Hybrid-PjBL is a learning that has the potential to better develop students' thinking skills.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these studies examine the increase of students' creativity in various countries (Isabekov & Sadyrova, 2018;Rambely et al, 2013). Several studies in Indonesia also reported similar results (Antika & Nawawi, 2017;Ummah, Inam, & Azmi, 2019). The increase in students' creative thinking skills after participating in PjBL further emphasizes the role of this learning in empowering thinking skills and various other 21st Century competencies (Bell, 2010;Kokotsaki, Menzies, & Wiggins, 2016;Takeda, 2016).…”
Section: Resultsmentioning
confidence: 87%
“…In connection with the importance of empowering creative thinking skills, microteaching lectures must be designed to be innovative learning-based lectures. Several learning models that can be used as references in empowering creative thinking skills are project-based learning (Antika & Nawawi, 2017;Putri et al, 2019;Wijayati et al, 2019;Yamin et al, 2020) and problem-based learning models (Birgili, 2015;Kardoyo et al, 2020;Khoiriyah & Husamah, 2018;Talat & Chaudhry, 2014;Zhou, 2012). Lecturers can raise problems before the Plant Microtechnique lecture begins.…”
Section: Resultsmentioning
confidence: 99%